ISOLATION OF NODULE-ASSOCIATED BACTERIA FROM Indigofera zollingeriana AND ITS CROSS INOCULATION TO MUNGBEAN - Priskila Sophia Hutapea; Luki Abdullah; Panca DMH Karti; I Anas (Buletin Ilmu Makanan Ternak, 2017)
Indigofera zollingeriana is a shrubby legume which highly accepted as fodder to animal ration because of its high protein content. As a legume, this plant could provide itself a nitrogen because of its symbiotic relationship with rhizobia. Moreover, there are some other bacteria could be found in root nodule which also supports plant growth. This experiment was aimed to find rhizobia or Nodule-Associated Bacteria from Indigofera zollingeriana and its cross-nodulation capability on mungbean (Vigna radiata). Indigofera zollingeriana root nodules were collected from three different locations. Total of 9 isolates were collected and cultured on Yeast Extract Mannitol Agar (YEMA). Isolates were also tested for nodulation on I. zollingeriana and mungbean. Five days old isolate were inoculated to I. zollingeriana and mungbean seed for approximately 30 minutes and then sown into sterile sand. This experiment was designed in completely randomized design with three replications. Colonies morphology, Gram`s nature, nitrogenase activity of asymbiotic isolates, nodules number, nodules fresh weight, were observed. Isolates showed a raised glistening white colonies. Most of isolates showed a gram negative, but JP1 and KF isolate were found to be a gram positive. All isolates possesed a nitrogenase activity. Nodulation test showed that all isolates could renodulate I. zollingeriana better than control. BM isolate, which had the lightest nodule fresh weight on I. zollingeriana, could increased nodulation  13.62% better than the uninoculated treatment. Different case was found on mungbean, only JM1 and BM isolate that could nodulate better than control.